2020
DOI: 10.3390/agronomy10040584
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experimental Experience with a Sprayable Biodegradable Polymer Membrane (SBPM) Technology in Cotton

Abstract: Preformed biodegradable and next generation sprayable biodegradable polymer membrane (SBPM) formulations, which biodegrade to non-harmful products (water, carbon dioxide and microbial biomass), have been introduced as an alternative to plastic mulch films in order to mitigate plastic pollution of the environment. In this preliminary field study on cotton (Gossypium hirsutum L.), a novel SBPM technology was compared to preformed slotted oxo-degradable plastic (ODP) mulch film and no mulch control (CON) in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Braunack et al (2021) found that BSM films increased the soil water content but did not affect tomato or watermelon (Citrullus lanatus) yield when compared with bare soil or plastic mulch film. Similarly, Braunack et al (2020b) reported no difference in cotton yield when comparing BSM films to bare soil and a solid plastic mulch film.…”
Section: Mean (Se)mentioning
confidence: 98%
See 1 more Smart Citation
“…Braunack et al (2021) found that BSM films increased the soil water content but did not affect tomato or watermelon (Citrullus lanatus) yield when compared with bare soil or plastic mulch film. Similarly, Braunack et al (2020b) reported no difference in cotton yield when comparing BSM films to bare soil and a solid plastic mulch film.…”
Section: Mean (Se)mentioning
confidence: 98%
“…Common challenges and limitations of these BSM films have included premature degradation, shrinking, drying, cracking, infiltration, or wicking into soil pore space, as well as insufficient weed suppression (Adhikari et al 2019;Braunack et al 2020a;Giaccone et al 2018;Immirzi et al 2009;Russo 1993;Shen and Zheng 2017). However, observed benefits of BSM films have included significant weed suppression (Braunack et al 2020a;Claramunt et al 2020;Giaccone et al 2018;Shen and Zheng 2017;Warnick et al 2006), increased soil moisture (Adhikari et al 2019;Braunack et al 2020a) and temperature (Braunack et al 2021), and crop yield and plant growth comparable to polyethylene plastic mulch film or bare soil (Braunack et al 2020b(Braunack et al , 2021Immirzi et al 2009;Shen and Zheng 2017).…”
mentioning
confidence: 99%
“…For this reason, SBPM may provide a more environmentally safe means of applying plastic mulch within intensive and broadacre settings (Braunack, Adhikari, et al, 2020;Johnston et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These concerns have renewed interest in developing effective, biodegradable and photodegradable mulches, as an alternative to early products developed in the 1970s and 1980s which were expensive and unpredictable in their breakdown. More recently, natural products such as sprayable biodegradable polymer membranes (SBPM) are being developed (Braunack, Adhikari, et al, 2020), but still require validation at a commercial scale.…”
Section: Introductionmentioning
confidence: 99%
“…A common practice of improving fruit and vegetable production is agricultural plastic mulching, which can modify soil temperatures [1], conserve moisture [2], reduce weed pressure [3] and increase yields [4][5][6]. Polyethylene mulch films (PEMs) are usually used in agriculture because of the low price and high durability, but the main drawback of PEMs is that it is non-degradable, and which has caused plastic film pollution and affected the planting environment [7][8][9].…”
Section: Introductionmentioning
confidence: 99%